Knowledge, preferences, practices, and attitudes about breastfeeding among postnatal mothers in Uttarakhand, India: a cross-sectional study - Jelly, Prasuna; Kodi, Malar; Sharma, Meenakshi; Sharma, Suresh K; Sharma, Rakesh (Indian Journal of Community Health, 2022)
Background: Breastmilk is the natural and safest first food for the newborn. It has nutritional, immunological, behavioural, and offers mother-infant bonding. Objective: The objective of the study was to explore the knowledge, practice, and attitudes of mothers towards breastfeeding. Material & Methods: A cross-sectional study was conducted among conveniently selected 950 postnatal mothers attending the immunization clinic and paediatric OPD with their children for vaccination and treatment of other minor illnesses from April 2018 to November 2019 in selected hospitals of Rishikesh, Uttarakhand. Mothers were face-to-face interviewed using structured knowledge, preference, practices, and attitude questionnaires about newborn breastfeeding. Tools were validated and tested for reliability. Results: The average knowledge scores (11.72±1.78) indicated that mothers have good knowledge about breastfeeding. Most mothers (81.45%) fed their babies with colostrum, and 82% were exclusively breastfeeding. It was also reported about top feeds like honey, coconut water, grape water, ghuttee, lactogen among about 20% of the participants. The average score of the Iowa Infant Feeding Attitude Scale (IIFAS) (58.11±6.44) lay in the range of neutral attitudes related to breastfeeding practices among the mothers. Conclusion: Breastfeeding practices were adequate among many mothers, but there were practices of throwing colostrum, topfeed baby and early initiation of weaning. Thus, it is necessary to create awareness among the mothers and their families about the correct practices of feeding the newborn baby; eventually, the attitude will change.